The Late-Scholastic and Austrian Link To Modern Catholic Economic Thought - Sirico, Robert (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2017)
This article deals with affinities between Catholic thought and theories of the Austrian school of economics. It is argued that one must rediscover the economic thinking of the late scholastics. The Austrian emphasis on subjectivity and choice offers the transmission of a body of thought that makes coherent, remarkable and strong the link between the old and new Catholic economy. The article ends with reappearance of these ideas in the modern Catholic economy. An outline of a scholarly tradition beginning in Scholasticism, through Carl Menger and the philosopher Franz Brentano, is traced to his reintegration into Catholic social teaching under Karol Wojtyla.